2011
DOI: 10.4103/1658-354x.82782
|View full text |Cite|
|
Sign up to set email alerts
|

Analgesic properties of a dexmedetomidine infusion after uvulopalatopharyngoplasty in patients with obstructive sleep apnea

Abstract: Background:Dexmedetomidine is an alpha2 -adrenergic agonist with sedative and analgesic properties. This study aimed to investigate if the use of a continuous dexmedetomidine infusion with i.v. morphine patient-controlled analgesia (PCA) could improve postoperative analgesia while reducing opioid consumption and opioid-related side effects.Methods:In this prospective randomized, double-blinded, controlled study, 39 patients with obstructive sleep apnea syndrome undergoing uvulopalatopharyngoplasty were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
4
36
1
Order By: Relevance
“…Dexmedetomidine has been found to reduce both intraoperative and postoperative opioid requirement due to its opioid sparing effect. [1415] In our study, we observed, an increase in the time to receive first rescue analgesia in dexmedetomidine group when compared to NS group. The mean time for rescue analgesia in Group NS was 50 min and all patients received rescue analgesia.…”
Section: Discussionsupporting
confidence: 47%
“…Dexmedetomidine has been found to reduce both intraoperative and postoperative opioid requirement due to its opioid sparing effect. [1415] In our study, we observed, an increase in the time to receive first rescue analgesia in dexmedetomidine group when compared to NS group. The mean time for rescue analgesia in Group NS was 50 min and all patients received rescue analgesia.…”
Section: Discussionsupporting
confidence: 47%
“…Patients undergoing UPPP and tonsillectomy experience unacceptable intense postoperative pain, especially during the first 24 h after surgery . So the treatment of postoperative pain after UPPP and tonsillectomy presents a challenge .…”
Section: Discussionmentioning
confidence: 99%
“…Uvulopalatopharyngoplasty (UPPP) with tonsillectomy is a common method for the treatment of moderate‐to‐severe obstructive sleep apnoea syndrome . Postoperative pain is a common problem . Adult patients undergoing UPPP with tonsillectomy experience an unacceptable level of intense postoperative pain, especially during the first 24 h after surgery .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations